Revitalizing Higher Education in Africa: A Review of Health Research ( in Social Science) in African Universities - A paper presented at the 2016 SASA Conference , Rhodes University, Grahamstown. - Obuaku-Igwe, Chinwe C. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
What is the agenda for health research in Social Sciences in African Universities? To what extent has university led research in the area of health revitalized higher education in Africa? This paper examines through a review of empirical literature, how university led health research in Social Sciences is repositioning African Countries/health systems for effective and efficient performance through generating and disseminating timely knowledge that resonates from the African context. It draws attention to how university-led social science research in health has contributed to the wider society and health system. It argues that the recognition of this in the health sector and by governments stimulates further research funding for university based researchers, however limited, thus creating an environment of energetic research activities, which, in the long run is significant in the revitalisation of higher education. The paper theorises the production of knowledge in the context of health research in the Social Sciences and how this contributes to the revitalizing of higher education in Africa.